Using Movement Activities in Engaging Young Learners - Eldina Iswandhary (Universitas Pendidikan Ganesha, 2021)
Activities including movements can make young learners understand something through their five senses. However, instead of accommodating them to learn physically, most of the teachers often tell young learners to stay still on their seat. Therefore, this article investigated on how movement activities can be used by the teachers to engage the young learners at school. In this study, library research method was conducted in collecting the data which is also analyzed by the researcher. Teaching young learners is not as easy as it seems. One of their characteristics is they like to learn through movement activities which can be done by seeing, hearing, touching and interacting with something. Unfortunately, this characteristic also can be a problem for teacher to engage them in the classroom activity since they can be easily distracted over things that they are curious about. There is one thing that the teacher could implement to make the students engage in the class which is by using movement activities. Instead pushing the students to stay still and keep silence, it is better to make use or utilize their characteristic as a way to learn. Some activities which are including movements like music or singing a song and playing games with some physical moves, total physical response activities, and some other activities which involve coloring, cutting, sticking, and any other movements activities could be done by the teacher inside or outside the classroom.